2020
DOI: 10.1186/s12889-020-09087-5
|View full text |Cite
|
Sign up to set email alerts
|

Practice and technique of using face mask amongst adults in the community: a cross-sectional descriptive study

Abstract: Background: The proper use of face mask comprises the correct practice and wearing technique and is important in preventing the spread of respiratory infections. Previous studies have addressed only the aspect of practice and failed to provide a detailed account of face mask usage amongst community-based populations. This study examined the practice and technique of using face mask amongst adults. Methods: A cross-sectional descriptive design was adopted. A quota sample of 1500 adults was recruited in Hong Kon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
79
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(102 citation statements)
references
References 15 publications
3
79
2
2
Order By: Relevance
“…Similarly, in the review of Bish and Michie [ 73 ], which identified the determinants of different protective behaviors practiced during swine flu pandemic, it was indicated that compliance to wearing face masks was associated with gender. The same observations were reported by Lee et al [ 74 ] in their study which stated that in all the required situations (including when taking care of family members with fever, when taking care of family members with respiratory infection, when visiting clinics during peak season or a flu pandemic, when visiting hospitals during peak season or a flu pandemic, and when having respiratory symptoms), females declared a higher frequency of using face masks than males.…”
Section: Discussionsupporting
confidence: 83%
“…Similarly, in the review of Bish and Michie [ 73 ], which identified the determinants of different protective behaviors practiced during swine flu pandemic, it was indicated that compliance to wearing face masks was associated with gender. The same observations were reported by Lee et al [ 74 ] in their study which stated that in all the required situations (including when taking care of family members with fever, when taking care of family members with respiratory infection, when visiting clinics during peak season or a flu pandemic, when visiting hospitals during peak season or a flu pandemic, and when having respiratory symptoms), females declared a higher frequency of using face masks than males.…”
Section: Discussionsupporting
confidence: 83%
“…But the current study was higher than with the study conducted in Hong Kong among adults in the community which was only 7.6 of the participants reported that they always wore face mask when taking care of family members with fever or respiratory infections. 20 With regard attitude of health professionals towards face mask utilization, in the current study, less than half 45.3% of the respondents had a positive attitude towards proper face mask utilization. This was much lower compared to the 18 This difference might be due to the difference in study area and tool, and similarly, it was lower compared to the study done in Malaysian public which accounted 83.1.…”
Section: Discussionmentioning
confidence: 56%
“…In the studies reviewed, most authors have reported some level of 'willingness' to wear masks in the community, with higher levels of compliance (or willingness) reported amongst women, older adults (aged > 50 years), the highly educated (results are inconclusive in some studies), married individuals, and adults with poor selfrated health and/or home duties [15][16][17][18][19][20][21]. In regard to gender, it has been suggested that males may perceive the use of masks as being un-"manly", and not use them due to variations in perceptions around health-related consequences [22]. However, not all studies have reported gender differences in relation to the use of masks, which may reflect the country of origin of the study (i.e., Australia and The Netherlands which do not have a culture of community mask use) [19,23].…”
Section: Personal Protective Measures Mask Usementioning
confidence: 99%